2021
DOI: 10.1177/0301006621992940
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Inhibition of Return Affected by Self-Prioritization Effect in Three-Dimensional Space

Abstract: Spatial inhibition of return (IOR) being affected by the self-prioritization effect (SPE) in a two-dimensional plane has been well documented. However, it remains unknown how the spatial IOR interacts with the SPE in three-dimensional (3D) space. By constructing a virtual 3D environment, Posner’s classically two-dimensional cue-target paradigm was applied to a 3D space. Participants first associated labels for themselves, their best friends, and strangers with geometric shapes in a shape-label matching task, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
(120 reference statements)
2
9
0
Order By: Relevance
“…While it goes beyond the current research to pinpoint what stages of information processing and through what mechanism cooperative contexts modulate inhibition of return in the joint spatial cueing task, our findings add to the long list of studies demonstrating endogenous modulation of inhibition of return effects (Birmingham et al, 2007;Bucker & Theeuwes, 2014;Jones et al, 2002;Lupiáñez et al, 2001;Pratt et al, 1998;Tipper & Kingstone, 2005). Our findings are consistent with previous research showing that beliefs about the social meaning of the cue alone suffice to modulate inhibition of return effects (Gobel et al, 2018;Gobel & Giesbrecht, 2020;Liu et al, 2021;Tufft et al, 2015). Future research is needed to investigate the specific mechanism underlying such social modulation of inhibition of return effects, for example, whether it is more strategic and effortful or implicit and effortless in nature.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…While it goes beyond the current research to pinpoint what stages of information processing and through what mechanism cooperative contexts modulate inhibition of return in the joint spatial cueing task, our findings add to the long list of studies demonstrating endogenous modulation of inhibition of return effects (Birmingham et al, 2007;Bucker & Theeuwes, 2014;Jones et al, 2002;Lupiáñez et al, 2001;Pratt et al, 1998;Tipper & Kingstone, 2005). Our findings are consistent with previous research showing that beliefs about the social meaning of the cue alone suffice to modulate inhibition of return effects (Gobel et al, 2018;Gobel & Giesbrecht, 2020;Liu et al, 2021;Tufft et al, 2015). Future research is needed to investigate the specific mechanism underlying such social modulation of inhibition of return effects, for example, whether it is more strategic and effortful or implicit and effortless in nature.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…Stereoscopic vision allows us to extract the 3-D spatial locations in depth based on which visuospatial attention can be shifted along the third dimension of visual space. Especially the inhibition effects showed that, the spatial IOR effect was different when the target appeared in near versus far depth plane (Chen et al, 2012;Liu et al, 2021;Wang et al, 2015Wang et al, , 2016Wang et al, , 2017. Specifically, under the invalid condition (the cue and target are in different positions), attentional reorienting to objects that unexpectedly appeared near observers was faster than reorienting to unexpected objects far away, so the former condition enlarged the IOR size, whereas the latter condition reduced the IOR size or removed the IOR effect completely.…”
Section: Introductionmentioning
confidence: 96%
“…Participants. Previous researchers using 3-D IOR paradigms employed sample sizes of 10-25 participants, and they obtained significant effect sizes from 0.11 to 0.49 (Casagrande et al, 2012;Chen et al, 2012;Liu et al, 2021;Theeuwes & Pratt, 2003;Wang et al, 2015;Wang et al, 2016;Wang et al, 2017). In addition to gathering this historical precedent, we used G* Power (v. 3.1.9.2) software (Faul et al, 2007) to estimate a required sample size for a repeated measures analysis of variance with an estimated effect size of f = 0.25, alpha of 0.05, and statistical power of 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Prior researchers, including some sport researchers, have generally used 2-D and static scenarios in IOR paradigms (Ding & Zhou, 2014;Lin et al, 2020;Ou et al, 2010;Redden et al, 2021). However, three dimensional or 3-D IOR has recently attracted high interest (Casagrande et al, 2012;Liu et al, 2021;Wang et al, 2015Wang et al, , 2016, and virtual reality (VR) technology has emerged as a superior method for studying IOR in scenarios with both depth and object movement (Bedir & Erhan, 2021). In fact, VR technology may provide optimal conditions for measuring athletes' attention abilities in depth and dynamic sport scenarios.…”
Section: Introductionmentioning
confidence: 99%